Hyaluronic acid and its use in non-hormonal therapy for the treatment of vaginal atrophy and the level of awareness about the disease itself among the women from the Podkarpackie Voivodeship - Glac, Agata; Musz, Kinga; Dobko, Katarzyna; Frącz, Gabriela; Kuliga, Klaudia; Sejnowska, Natalia; Socha, Agnieszka; Surowiec, Agata; Śnieżek, Kinga; Zając, Anna (Quality in Sport, 2023)
Introduction: Hyaluronic acid is the ingredient contained in the composition that has the ability to bind water, found in the cornea, synovial fluid and cartilage stroma. Its properties are suitable for use in an increasing range of fields, both aesthetic and in treatments focusing on the treatment of vaginal atrophy. Aim of the study: The aim of the study was to collect and analyze publications on the use of hyaluronic acid in the treatment of vaginal atrophy and assessment of the level of knowledge among women about this disease. Materials and methods: The research material was collected using an anonymous online survey. The obtained results were analyzed and verified on the basis of scientific literaturę and statistically processed using Microsoft Office Excel. Results: 59,7% of the respondents knew the term "vaginal atrophy" and 64,2% were able to correctly determine which of the hormones (estrogen) is the main cause of this condition. 59,7% of women indicated that they regularly undergo examinations and perform cytology every year, 29,9% indicated that they have examinations and visits "once in 2 years", 6% - "once in 3 years", the answers "less than once in 3 years” was given by 4,5% of the respondents. 85,7% of the surveyed women have never noticed any symptoms of vaginal atrophy and 85,9% believe that there are effective forms of treating this disorder. Conclusions: Awareness among women about vaginal atrophy, both those with medical education and women in other professions, is at a moderate level. Many women do not talk to their doctor about this not because of the feeling of shame, but also because of the lack of information and preventive measures. The progressive nature of vaginal atrophy should encourage clinicians to routinely engage in an open dialogue with patients about genitourinary health.